Enhancing prospective teachers’ creative thinking skills: A study of the transition from structured to open inquiry classes - Agus Ramdani; I Putu Artayasa; Muhammad Yustiqvar; Nina Nisrina (LPMPP Universitas Negeri Yogyakarta, 2021)
Creative thinking skills are considered to have a positive correlation with students’ academic achievement. Thus, they need to be developed through the learning process. To successfully develop these skills, an appropriate learning model is needed. This research aims to determine the improvement of the creative thinking skills of prospective teachers who learned using structured, guided, and open inquiries. This quasi-experimental research used an untreated control group design with pretest and posttest. A total sample of 118 students was selected and distributed into structured, guided, and open inquiry classes. The research instrument consisted of 18 creative thinking skill items applied to the pretest and posttest. The data analysis was performed using ANCOVA and LSD tests. The results show that the mean score of the open inquiry class was higher and significantly different compared to those of the other two classes. However, the mean scores of the two classes were not significantly different. Therefore, it can be concluded that the implementation of the open inquiry model led to a higher increase in creative thinking skills compared to those of the structured and guided inquiry models.